Case Report: Successful use of emapalumab in adult B-cell acute lymphoblastic leukemia experiencing severe neurotoxicity and hemophagocytic lymphohistiocytosis-like features after CAR-T cell therapy - Manghisi, Beatrice; Cotilli, Giulia; Fedele, Marilena; Perfetti, Paola; Terruzzi, Elisabetta; Verga, Luisa; Borin, Lorenza Maria; Carrer, Andrea; Fumagalli, Monica; Ferrari, Maria Beatrice; Moretti, Alex; Rona, Roberto; et al. (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR)-T cell therapy is a powerful adoptive immunotherapy associated with significant toxicity, including cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). As CAR-T usage expands, hyperinflammatory toxicities resembling hemophagocytic lymphohistiocytosis (HLH) syndrome are increasingly recognized. Immune effector cell-associated HLH-like syndrome (IEC-HS) describes HLH-like symptoms attributable to CAR-T cell therapy, often presenting as CRS resolves. Treatments for IEC-HS are adapted from primary HLH, including corticosteroids, the recombinant human interleukin (IL)-1 receptor antagonist anakinra and the Janus Kinase inhibitor ruxolitinib. Emapalumab, an anti-IFN-γ antibody, is promising but underexplored in adult IEC-HS cases. We report an adult B-cell acute lymphoblastic leukemia (B-ALL) patient treated with brexucabtagene autoleucel (brexu-cel). The patient developed CRS, refractory neurotoxicity, and IEC-HS with worsening multiorgan failure and hyperinflammatory markers. Treatment included tocilizumab, high-dose corticosteroids, anakinra, siltuximab, and ruxolitinib. Despite aggressive management, hyperinflammation and neurotoxicity persisted. Emapalumab was initiated on day +11, resulting in normalization of the biochemical parameters and full neurological recovery by day +21. The patient recovered from IEC-HS and underwent allogeneic stem cell transplantation. This case highlights the role of emapalumab in managing refractory IEC-HS and persistent neurotoxicity in adults, underscoring the need for targeted interventions in severe CAR-T complications.